+0  
 
0
66
1
avatar

solve for x

\(\dfrac{\sqrt{3x}-4\sqrt{3}}{\sqrt{x}-\sqrt{2}}=\dfrac{2\sqrt{2x}+\sqrt{2}}{\sqrt{6x}-2\sqrt{3}}\)

 Mar 19, 2020
 #1
avatar+111360 
+1

Cross-multiply

 

[ √(3x) - 4√3]  [ √(6x) - 2√3]   = [ √x  - √2] [ 2√(2x)  + √2 ]     simplify

 

√ (3x * 6x)  - 4√(3 * 6x) - 2√(3 * 3x) + 8√(3 * 3)  =  2√(2x * x)  - 2√(2* 2x)  + √(2x)  - √(2*2)

 

√(18x^2)  - 4√(18x) - 2√(9x) + 8√9  =  2x√2 - 4√x + √(2x) - 2 

 

3x√2  - 12√(2x) - 6√x + 24  =   2x√2 - 4√x + √(2x) - 2

 

x√2 - 13√(2x) - 2√x + 26  =  0 

 

√(2x) [ √x - √2 ]  =   13√(2x) - 26

 

√(2x)  [ √x - √2) ]=  13√(2x) - 13(2) 

 

√(2x) [ √x - √2)  =  13√2  [ √x - √2]

 

[ √x - √2]  [ √(2x) - 13√2 ]   =   0

 

[ √x - √2] (√2) [ √(x) - 13 ]   =   0      divide out  √2

 

[ √x - √2]  [ √(x) - 13 ]   =   0

 

So  we  have  that

 

√x - √2  =  0        or       √x - 13  = 0

    x   =  2                       √x   = 13             square both sides

 

    x  = 2          or          x   =169     

 

Reject  x  = 2   since it makes  an original denominator    =    0

 

So.....the solution is that   x   =169

 

 

cool cool cool

 Mar 19, 2020

20 Online Users

avatar